An Exegesis of Teaching About Christian Maturity in James 1:1-15 - Philip Suciadi Chia; Sjanette Eveline (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
When you experience a new birth, you will not automatically experience spiritual maturity. To achieve the journey to spiritual maturity requires a process. There is wisdom that will be the measure.James 3:13-18 offer an answer. James describes that wisdom from above is pure, peaceable, gentle, reasonable, full of mercy, good fruits, unwavering, without hypocrisy, righteousness, and peace. Wisdom, in the book of James, benefits individual and community (chapter 1 and 3). With wisdom will go through the various struggles of life.